Retraction Notice: Ruang Budaya Pada Proses Daur Hidup (Pernikahan) dan Tradisi Wiwit di Desa Sumber Polaman, Lawang Jawa Timur : Vol 3 no 1 2017 - editorial editorial (EMARA: Indonesian Journal of Architecture, 2021)
We hereby announce that the article entitled "Ruang Budaya Pada Proses Daur Hidup (Pernikahan) dan Tradisi Wiwit di Desa Sumber Polaman, Lawang Jawa Timur" published in Vol 3 No in 2017 has been withdrawn / retracted at the request of the author on October 13, 2021. The reason for the withdrawal is because it is indicated that the paper quoted without mentioning the source (misconduct) on the article "Nilai Kosmologi Pada Tata Spasial Pada Permukiman Desa Kapencar Lereng Gunung Sindoro Wonowsobo (https://journal.ugm.ac.id/mft/article/view/654) Thus, we convey this notice so that it can be used properlyThis withdrawal was made at the request of the author